Pengaruh Kualitas Pelayanan Akademik Febiiain Fattahul Muluk Papua Terhadap Loyalitas Mahasiswa Dengan Kepuasan Mahasiswa Sebagai Variabel Intervening. - Rasyidi, Ahlan; Risamasu, Ferdinand; Kambu, Arius Andreas (Adhigana Papua: Jurnal Ilmiah Magister Manajemen, 2024)
This research aims to analyze the influence of the quality of FEBI IAIN Fattahul Muluk Papua's academic services on student loyalty with student satisfaction as an intervening variable both directly and indirectly. The research method used is quantitative with an explanatory design. The sampling technique used purposive sampling with a sample size of 123 respondents. Data collection techniques are observation, interviews, and distributing questionnaires. The data analysis method used in this research is Structural Equation Modeling (SEM) with SmartPLS software. The research results show that academic service quality has a significant effect on student loyalty, academic service quality has a significant effect on student satisfaction, student satisfaction has a significant effect on student loyalty, and student satisfaction can be an intervening variable between academic service quality and student loyalty.